Geoprocessing applied to fire risk mapping - Oliveira, Víncler Fernandes Ribeiro; da Silva, Edson Rodrigo Dos Santos; da Silva, Bruno Henrique Machado; Vick, Erivelton Pereira; Lima, César Gustavo da Rocha [UNESP]; Bacani, Vitor Matheus (Revista Brasileira de Geografia Fisica, 2020)
Forest fires are a real threat to maintaining the biodiversity of natural and anthropogenic environments, imposing severe financial, social and even human damage to the affected areas, so identifying the areas most likely to occur becomes a key issue for planning and management environmental. The objective of this study was to identify the areas that present a fire risk in Coxim-MS. The methodological procedures consisted of the weighted combination of the fuzzified variables: slope, aspect, rainfall, highways, urban area, hydrographic network, land use and land cover and hotspot. The results showed concentration of the high fire risk in the central region and in a small part in the west, mainly influenced by hotspots, low rainfall, sharp drainage distance and land use and land cover. It was also identified a predominance of medium risk, which occupied 86.73% of the total area of the municipality, while low risk occupied 10.17% of the total. The observed results can contribute to the prevention and fight against fires, providing subsidies for the design of strategies and public policies for the planning and planning of the territory.
Geoprocessamento aplicado ao mapeamento de risco a incêndios
Keywords: Cerrado; Geotechnologies; Heat sources; Mato Grosso do Sul; Pantanal wetland